La competencia por la tierra entre la agricultura y la ganaderia en el minifundio costeno - Boering, S; Janssen, W. (International Center for Tropical Agriculture, 1984)
The results of a case study conducted in Betulia (Sucre, Colombia) in May-Dec. 1983 to evaluate the competition for land between cassava cultivation (monocropped or in association with maize or yam) and cattle raising are discussed. In general, profits from cassava either in association or in monoculture are much higher than for cattle raising. Regarding labor requirements, cassava cultivation and cattle raising are equally attractive from an economic viewpoint. The cash flow is almost continuous for cattle raising, while for associated and monocropped cassava it happens during 6-7 and 2-4 mo. of the year. Cattle raising is less risky than cassava cultivation. In terms of nutrition, both activities are important. The factor explaining the importance of cattle raising is its role as source of capital for the farmer. Although cassava drying plants would reduce marketing risks and the need to have cattle as a buffer, farmers are not willing to reduce their herds. Recommendations on the future development of both activities are given. (CIAT)